U.S. Return Migration and the Decline in Southern Black Disadvantage, 1970–2000*. (5th March 2018) - Curtis, Katherine J.
Abstract : Objective: This study investigates how the Return Migration altered racial inequality in poverty in the American South. Methods: I disaggregate southern poverty into its separate constituents using household data from the Integrated Public Use Microdata Series (IPUMS) for 1970 through 2000. Results: The prevalence of poverty declined most dramatically for black southern households and the racial gap in poverty narrowed to the extent that previous substantial regional differences disappeared. A central focus is the contrast between higher poverty and inequality among migrants who returned to their birth state relative to other southern‐born migrants who returned to the South. Conclusions: The migration experience is diverse and has conflicting consequences for racial inequality; for some, migration maintained economic vulnerability. Given the complex force of migration, I conclude that a nuanced theoretical approach to migration that gives weight to economic and noneconomic motivations is critical to understand the racial dimensions of migration and the associated changes in racial inequality.